Simulação de sistemas de radar de penetração de solo (GPR) via formasdiferenciais - Alex Sander de Moura (2012)
The main interest of this thesis is the use of a numerical method applied to ground penetrating radar (GPR) problems using tetrahedral mesh. To develop this proposal it is used the language of differential forms applied to electromagnetism. This choice was made given the fact that the exterior calculus of differential forms provides a mathematical framework for the theory of electromagnetic fields that combines muchof the generality of the tensor analysis with the computational simplicity and concreteness of the vector calculus. It can be seen that although the calculus of differential forms is in many aspects similar to thevector calculus, it is in fact more general than the vector notation.The following contributions of this work are: Development of a sparse approximation technique for the inverse of Hodge matrices. Development of an absorbing boundary condition to deal with lossy media.These contributions will enable the application of the theory of differential forms for the simulation of soil penetrating radar systems.